Feminisme dalam Film Penyalin Cahaya Karya Sutradara Wregas Bhanuteja - Fatimah Zahro; Nina Queena Hadi Putri (Universitas Palangka Raya, 2025)
The film Penyalin Cahaya by Wregas Bhanuteja highlights the issues of feminism, sexual violence, and the culture of victim blaming that are still rampant in Indonesian society. This study aims to analyze the representation of feminism in the film Penyalin Cahaya using Roland Barthes' semiotic analysis method. The results of the study show that this film represents feminism through various aspects, including criticism of the patriarchal system that protects perpetrators of sexual violence, as well as how the culture of victim blaming is still a major challenge for victims. The conclusion of this study is that Penyalin Cahaya not only functions as a work of art, but also as an advocacy medium that raises public awareness about the importance of supporting victims of sexual violence and fighting patriarchal culture.